DEVELOPMENT AND VALIDATION OF AN INTEGRATED PROBLEM BASED LEARNING AND E-LEARNING MODEL TO ENHANCE LITERARY ANALYSIS SKILLS IN HIGHER EDUCATION - atiq atiq; Hassanuddin Fatsah; Harto S. Malik; Ellyana Hinta (ASMARALOKA : Jurnal Bidang Pendidikan, Linguistik dan Sastra Indonesia, 2026)
This study aims to develop and examine the effectiveness of an integrated Problem-Based Learning (PBL) and e-learning model in enhancing students’ literary analysis skills in the Literary Theory and Criticism course. The study is grounded in the identified gap between students’ conceptual understanding of literary theory and their ability to apply it critically in textual analysis. Employing a Research and Development (R&D) design with a mixed-method approach, the research was conducted in the English Literature Study Program at Muhammadiyah University of Gorontalo. The development process followed the ADDIE framework, encompassing the stages of analysis, design, development, implementation, and evaluation. Nine fourth-semester students participated in a limited trial using a one-group pretest-posttest design. Data were collected through validation sheets, classroom observations, reflective journals, and literary analysis essay tests. Quantitative data were analyzed using descriptive statistics, normalized gain (N-Gain), and paired-sample t-tests, while qualitative data were examined through thematic analysis. The findings indicate that the developed model meets three essential criteria of educational product quality: validity, practicality, and effectiveness. Expert validation results demonstrate high levels of content and construct validity. The implementation of the model revealed strong student engagement and positive responses toward digitally supported collaborative learning. Statistical analysis shows a significant improvement between pretest and posttest scores, with high N-Gain categories across all indicators. The integration of PBL and e-learning fosters student-centered learning, critical thinking, collaborative inquiry, and the strengthening of digital literacy skills.